High-mechanical-strength polyimide aerogels crosslinked with 4, 4′-oxydianiline-functionalized carbon nanotubes. (April 2019) - Zhu, Zhaoxian; Yao, Hongjun; Dong, Jinxin; Qian, Zhen; Dong, Wei; Long, Donghui
Abstract: Polyimide (PI) aerogels are among the most promising organic aerogels as thermal insulation materials, but brittle compressive strength severely limits their practical applications. Herein, we develop a novel procedure to prepare lightweight and strong PI aerogels crosslinked with 4, 4′-oxydianiline (ODA)-functionalized carbon nanotubes (CNTs). PI gels could be produced by cross-linking anhydride capped polyamic acid oligomers, followed by chemical imidizing. CNTs, treated through ODA functionalization, not only provide affinity with solvents, but also react with terminal anhydride groups of PAA to form strong covalent bonding with polymer chains. These modified CNTs could serve both as rigid crosslinker and linear reinforcement, which can effectively suppress the shrinkage of aerogels during preparation process. The obtained aerogels possess developed mesoporous structure with density as low as 0.107–0.121 g cm −3 . The addition of only a small amount of CNTs could increase the mechanical properties of PI aerogels drastically, e.g. a 19-fold increase in Young's modulus and 15-fold increase in yield strength. The addition of CNTs could also improve thermal stability, with only a slight increase in thermal conductivity from 0.018 W m −1 K −1 to 0.023 W m −1 K −1 at room temperature. These high-mechanical-strength aerogels with high thermal stability and low thermal conductivity render them potential candidates for various aerospace applications. Graphical abstract: We develop a novel method towards the modification of CNTs by the introduction of -NH2 from ODA, which acts as a chemical cross-linker site for PI as show in Figure a . Figure b depicts the process followed for the synthesis of CNTs-PI aerogels. 3, 3′, 4, 4′-biphenyltetracarboxylic dianhydride (BPDA) and 4, 4′-oxidianiline (ODA) are chosen to prepare the linear poly(amic acid) (PAA), because their aromatic substituents hinder the rearrangement of the oligomer chains. Image 1